Thermopriming triggers splicing memory in Arabidopsis. (27th February 2018) - Ling, Yu; Serrano, Natalia; Gao, Ge; Atia, Mohamed; Mokhtar, Morad; Woo, Yong H; Bazin, Jeremie; Veluchamy, Alaguraj; Benhamed, Moussa; Crespi, Martin; Gehring, Christoph; Reddy, A S N; et al.
Abstract : Thermopriming induces genome-wide differential gene expression and alternative splicing patterns, and establishes a 'splicing memory' that helps plants to survive subsequent and otherwise lethal heat stress. Abstract: Abiotic and biotic stresses limit crop productivity. Exposure to a non-lethal stress, referred to as priming, can allow plants to survive subsequent and otherwise lethal conditions; the priming effect persists even after a prolonged stress-free period. However, the molecular mechanisms underlying priming are not fully understood. Here, we investigated the molecular basis of heat-shock memory and the role of priming in Arabidopsis thaliana . Comprehensive analysis of transcriptome-wide changes in gene expression and alternative splicing in primed and non-primed plants revealed that alternative splicing functions as a novel component of heat-shock memory. We show that priming of plants with a non-lethal heat stress results in de-repression of splicing after a second exposure to heat stress. By contrast, non-primed plants showed significant repression of splicing. These observations link 'splicing memory' to the ability of plants to survive subsequent and otherwise lethal heat stress. This newly discovered priming-induced splicing memory may represent a general feature of heat-stress responses in plants and other organisms as many of the key components are conserved among eukaryotes. Furthermore, this finding could facilitate the development of novel approaches to improve plant survival under extreme heat stress.